2013
DOI: 10.1039/c3cp50191d
|View full text |Cite
|
Sign up to set email alerts
|

Binding energy determination in a π-stacked aromatic cluster: the anisole dimer

Abstract: The binding energies of the neutral and positively charged anisole dimer have been determined in molecular beam-laser spectroscopy experiments. This is the first report on the direct experimental determination of the binding energy for an aromatic cluster in π stacked configuration. The anisole dimer is formed by two anisole molecules superimposed in a planar arrangement and it has been proposed as a model system in which the π-stacking interaction, among other intermolecular forces, plays a relevant role. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…In order to improve the experimental determination of the binding energy of the anisole dimer we have increased the sensitivity by measuring the total ion yield for both anisole dimers and anisole fragments in a conventional Wiley‐McLaren time‐of‐flight mass spectrometer. Previous experiments were performed in a velocity mapping ion imaging spectrometer, which allows the measurement of the momentum of the ions, but accepts only a few ions per laser shot 1. The present spectrometer integrates the signal from all ions of the same mass and thus accepts a much larger number of ions arriving on the detector at the same time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to improve the experimental determination of the binding energy of the anisole dimer we have increased the sensitivity by measuring the total ion yield for both anisole dimers and anisole fragments in a conventional Wiley‐McLaren time‐of‐flight mass spectrometer. Previous experiments were performed in a velocity mapping ion imaging spectrometer, which allows the measurement of the momentum of the ions, but accepts only a few ions per laser shot 1. The present spectrometer integrates the signal from all ions of the same mass and thus accepts a much larger number of ions arriving on the detector at the same time.…”
Section: Methodsmentioning
confidence: 99%
“…The dissociation energy ( D 0 ) in noncovalently bound molecular complexes and clusters in the gas phase represents their most important fundamental characteristic. Experimental determination of this quantity is not easy as it cannot be measured directly 1. 2 Experimental evaluation of the binding energy usually requires a molecular beam setup combined with multiple spectroscopic methods for inducing and detecting the fragmentation of the complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excitonic splitting between the S 1 and S 2 states occurs which has been measured to be 14 cm −1 . 262 The dissociation energy has been determined using VMI (velocity mapping ion imaging) in 2013, 36 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 zero-point-corrected CCSD(T)/CBS dissociation energy D 0 = 21.1 ± 0.2 kJ/mol. 37 6 Summary and Outlook 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Due to the recent improvements o...…”
Section: Complexes With Anisolementioning
confidence: 99%
“…A similar discrepancy was encountered also in the study of the anisole dimer, where the first observed dissociation channel in the ionic state resulted in the determination of the ground S 0 state dissociation energy being about 2000 cm À1 higher than the calculated value. 25 Further analysis revealed that the dissociation process was already starting at much lower energies, even if with a much lower efficiency. 26 We believe that all these differences can be explained as a consequence of the Franck-Condon factor for the S 0 -S 1 -ion excitation process: the aromatic ring dimensions are increasing with electronic excitation/ionization and the aromatic CQC stretching modes have a vibrational frequency of around 1000 cm À1 .…”
mentioning
confidence: 99%